Adherence to standard nursing protocols on nasogastric tube feeding in a secondary referral hospital in Ghana: comparing self-ratings by professional and auxiliary nurses - Robert Kaba Alhassan; Richard Tsikata; Richard Naatu Tizaawaw; Prince Asante Tannor; Perpetual Praba Quaw; Cecilia Aba Ata Awortwi; Martin Amogre Ayanore; Agani Afaya; Solomon Mohammed Salia; Japiong Milipaak; Prudence Portia Mwini-Nyaledzigbor (BMC, 2019)
Abstract Background Data on nurses' adherence to standard protocol on nasogastric (NG) tube feeding remain scanty in Ghana even though patients in critical medical conditions are routinely managed using this procedure. This study explored self-rated adherence to standard protocols on NG tube feeding among professional and auxiliary nurses and the perceived barriers impeding compliance to these standard protocols. Methods This is a descriptive analytical cross-sectional study among professional (n = 89) and auxiliary (n = 24) nurses in a major referral hospital in one of the ten administrative regions in Ghana. Four-point Likert scale was used to ascertain the level of adherence to standard guidelines on nasogastric tube, ranging from 4 "Very large extent" to 1 "Very little extent". Wilcoxon Mann-Whitney test and univariate ordered logistic regression tests (proportional odds models) were performed to determine the odds of higher self-ratings among professional and auxiliary nurses. Results Overall, the odds of higher self-ratings on adherence to standard nursing protocols on NG tube feeding was higher among auxiliary nurses than professional nurses (OR = 2.76, p = 0.031) after adjusting for age, gender, education and years of work experience. Key barriers to adherence to standard protocols on NG tube feeding were: limited opportunities for in-service trainings and insufficiency of NG tube feeding protocols on the wards. Conclusion There is the need for more routine in-service trainings for nursing staff to update their knowledge on NG tube feeding. Hospital management should also make current nursing protocols available to nurses to guide their practice alongside routine onsite supervision of nurses.